Preoperative H. pylori Eradication Therapy Facilitates Precise Delineation in Early Gastric Cancer with Current H. pylori Infection - Yan, Zhiyu; Zou, Long; Wang, Qiang; Zhang, Shengyu; Jiao, Yuhao; Xiong, Dingkun; Jiang, Qingwei; Guo, Tao; Feng, Yunlu; Wu, Dongsheng; Lai, Yamin; Yan, Xuemin; et al. (Digestive diseases (Basel), 2024)
Introduction: Early gastric cancer with current Helicobacter pylori infection (HpC-EGC) is common, but it is still unclear whether H. pylori eradication therapy (Hp-ET) or endoscopic submucosal dissection (ESD) should be performed first. We evaluated Hp-ETs short-term effects on horizontal boundary delineations of HpC-EGC in ESD. Methods: Prospectively enrolled HpC-EGC patients were randomly assigned to eradication or control groups. Operation scopes of HpC-EGC lesions were delineated with marking dots at 5 mm out of the endoscopic demarcation line by an independent endoscopist, unaware of eradication status, before formal circumferential incision. As representatives, precise delineation rate, the shortest distance of all marking dots to the pathological demarcation line in all slices of one intact resected specimen (D min ), and negative marking dot specimen rate were examined. Results: Twenty-three HpC-EGC patients (25 lesions) were allocated to eradication group and 26 patients (27 lesions) were allocated to the control group with similar eradication success rates and all were differentiated type. With improving background mucosa inflammation after Hp-ET and similar gastritis-like epithelium rates, 10 lesions (40.0%) in the eradication group were of precise delineation compared to control group with 2 lesions (7.4%) (relative risk = 5.40, 95% CI 1.31–22.28). D min of eradication and control groups were 4.17 ± 2.52 mm and 2.67 ± 2.30 mm (p = 0.029), accompanied by 4 (14.8%) and none (0.0%) specimens that exhibited positive marking dots (p = 0.11), respectively. Conclusion: For HpC-EGC patients, administrating eradication medication before ESD is beneficial for the precise delineation of lesions and reducing the risk of positive horizontal resection margins.